Kejadian Stunting Balita Usia 24-60 Bulan Di Desa Karangwinongan Kecamatan Mojoagung Jombang - Hariyani, Tintin (STIKES dan AKZI Karya Husada Kediri, 2025)
Toddlerhood is an important age in a child's physical growth and development. Therefore, this is a period where there is a very rapid growth and development process, so that toddlers need adequate nutritional intake. The condition of nutritional adequacy has a significant impact on sustainable health conditions in the future. Thus, the aim of this research is to determine the relationship between maternal knowledge about balanced nutrition and the incidence of stunting in toddlers aged 2 4-60 months in PMB Sri Wahyuningsih, Karangwinongan Village, Mojoagung District, Jombang Regency.This type of research is an analytical survey with a cross sectional approach. Independent variable: mother's knowledge about balanced nutrition, dependent variable: stunting. The population of all toddlers aged 24-60 months in Sri Wahyuningsih Private Midwifery Practice , Karangwinongan Village, Mojoagung District, Jombang Regency is 270 toddlers, with the sampling technique: simple random sampling, a sample of 161 toddlers was obtained. The measuring instruments used were questionnaires and observations, the results of which were analyzed using the chi square statistical test with a significant standard (α=0.05. The research results showed that almost all respondents' maternal knowledge about balanced nutrition was in the good category (78.5%), and almost all of the respondents' incidence of stunting was in the normal category (70.8%). Based on the chi square statistical test, it was found that the p-value was (0.000) < (α = 0.05), so H1 was accepted, which means that there was a significant relationship between respondents' knowledge about balanced nutrition and the incidence of stunting in toddlers aged 24-60 months. Good knowledge about balanced nutrition has a high probability that there will be no risk of stunting in toddlers, and conversely, good knowledge about balanced nutrition has a high probability that there will be no risk of stunting in toddlers.